2020
DOI: 10.47489/p000s342z7491-4mc
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience with Laparoscopic Nephrectomy at Services Hospital Lahore

Abstract: Introduction: Nephrectomy means removal of kidney. Laparoscopic nephrectomy is an effective way to remove a diseased or cancerous kidney. Nephrectomy is performed to treat malignant or benign tumors of the kidney and symptomatic non functioning kidney. Laparoscopic nephrectomy is performed through transperitoneal or retroperitoneal approach. Aims & Objectives: To determine the initial experience of laparoscopic nephrectomy. Place and duration of study: Department of Urology, Services Hospital, Lahore fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…16,17 However, in the study by Farooq M et al, the majority of patients were females, with 56 percent being female and 44 percent being male. 1 In our study most common cause of nonfunctioning kidney was stone disease 22% followed by PUJO 22.50% which is almost similar to other studies but in our study 12.50% patient had small kidney and 10 % had grossly hydronephrotic kidney due to distal ureteric stone which is different from other studies. 9 The average hospital stay in our study was 3.15 days, with a 0.94-day standard deviation.…”
Section: Laparoscopic Nephrectomysupporting
confidence: 74%
See 2 more Smart Citations
“…16,17 However, in the study by Farooq M et al, the majority of patients were females, with 56 percent being female and 44 percent being male. 1 In our study most common cause of nonfunctioning kidney was stone disease 22% followed by PUJO 22.50% which is almost similar to other studies but in our study 12.50% patient had small kidney and 10 % had grossly hydronephrotic kidney due to distal ureteric stone which is different from other studies. 9 The average hospital stay in our study was 3.15 days, with a 0.94-day standard deviation.…”
Section: Laparoscopic Nephrectomysupporting
confidence: 74%
“…These findings were consistent with prior studies in that the right side was more frequently observed than the left. 1,13 In our study, there were 13 men and 27 women patients, or 67.5 percent of the total (32.5 percent). Regarding the results of laparoscopic nephrectomy, studies by Khan MM et al and Piyush Singhania et al reported that there were more male patients than female patients in both studies.…”
Section: Laparoscopic Nephrectomymentioning
confidence: 64%
See 1 more Smart Citation
“…These techniques are known to show similar oncological results. Compared to open surgery, laparoscopic nephrectomy has less hospital stay, earlier return to daily life, and less painkiller use [ 4 ]. Although laparoscopic nephrectomy has a longer operation time compared to open nephrectomy in many studies, it is seen that the time decreases as experience increases [ 5 ].…”
Section: Introductionmentioning
confidence: 99%